Integrating Scientific Approaches into Adobe Animate- Assisted Interactive Media: Enhancing Geometric Spatial Skills for Secondary Education - Ani Afifah; N. Zumro (Journal of Teaching and Learning Mathematics, 2026)
This study aims to develop interactive learning media based on Adobe Animate integrated with a scientific approach, specifically focusing on flat-sided solid shapes such as cubes and cuboids. Employing the ADDIE development model—comprising Analysis, Design, Development, Implementation, and Evaluation—the research involved 32 eighth-grade students at MTsN 6 Pasuruan. The results indicate that the developed media fulfills high standards of quality, categorized as "Very Valid" with scores of 3.36 from media experts and 3.48 from material experts; "Very Practical" with a student response rate of 92.1%; and "Very Effective" with a classical completion rate of 87.5% (28 out of 32 students). Ultimately, the study concludes that integrating a scientific approach into digital media effectively facilitates students' constructivism, thereby enhancing their understanding of abstract geometric concepts.